Through-Mask Electrochemical Micromachining of Aluminum in Phosphoric Acid. Issue 9 (1st January 2017) - Baldhoff, T.; Nock, V.; Marshall, A. T.
Abstract : Aluminum micro-channels have been machined in phosphoric acid via mass-transfer limited electrochemical dissolution through photoresist masks. The results of shape evolution experiments using a rotating disk electrode are presented in terms of the dimensions, shape profile and uniformity of the machined micro-channels. The influences of applied potential, cumulative passed charge and hydrodynamic conditions on the shape evolution process are discussed. Experimental results are compared with a shape evolution model assuming the rate of aluminum removal is solely controlled by diffusive mass transfer. The degree of agreement between experimental and simulated results depends mainly on the hydrodynamic conditions in the electrochemical cell and indicates a shift from purely diffusive to mixed convective-diffusive mass transfer. The feasibility of electrochemical aluminum micromachining is demonstrated by fabricating microfluidic test structures with well-defined geometries and smooth surfaces.